PROTOTYPE SISTEM KONTROL MUROTTAL MASJID BERBASIS ARDUINO PADA MASJID NURUL FALAH JAMPEA KABUPATEN BANTAENG - Irdayanti (Jurnal Sistem Informasi dan Komputer (JSIKOM), 2020)
This study aims (1) to create an arduino-based murottal control system at Nurul Falah Jampea Mosque, Bantaeng Regency. (2) To implement arduino in the mosque's murrotal control system at the Nurul Falah Mosque in Jampea, Bantaeng Regency. This research uses the Action Research method with data collection techniques such as observation, interview and document collection methods. The results of this study indicate that (1) The prototype design of the arduino-based mosque murottal control system uses Real Time Clock (RTC) to set the murottal for 15 minutes and the 5-minute prayers that are processed by Arduino Uno based on the five-time prayer schedule. As well as using MP3s to play files chanting the verses of the Holy Qur'an and blessings through speakers and all these conditions will be displayed by Liquid Crystal Display (LCD). (2) The implementation of the arduino-based mosque murottal control system prototype can be used to maintain the accuracy of the five-time prayer schedule and can be applied to mosques whose murottals still use manual systems.